Giant dielectric properties of CaCu3Ti4O12 (Li,Ti) -doped NiO composites subjected to postsintering annealing and compressive stress - Prasit Thongbai (2018)
We report the effects of postsintering annealing in argon and compressive prestress on the giant dielectric properties of CaCu3Ti4O12- Li0.3Ti0.02Ni0.68O composites in the frequency range from 100 Hz to 1 MHz. After postsintering annealing, all compounds investigated still display a Debye-like relaxation, which can be interpreted based on the Maxwell-Wagner model. The dielectric behavior and the effect of compressive prestress of CaCu3Ti4O12and CaCu3Ti4O12- Li0.3Ti0.02Ni0.68O after annealing are closely related to the oxygen vacancies in the grain boundaries. © 2008 American Institute of Physics.